Polish and German Competition Policy in the Light of Ordoliberalism and a Concept of Social Market Economy (Economic and Political Thought, 2013)
Issues connected with competition policy are among the main aspectsof ordoliberalism and a concept of social market economy. Unlike otherneoliberals, ordoliberals expressed opinions that free competition, exemptfrom the control of the state, is a factor that endangers the free market economicsystem. The aim of the article is to carry out a comparative analysisof the contemporary Polish and German competition policies in the light ofordoliberalism and a concept of social market economy. The first part of thearticle is devoted to theoretical issues necessary to carry out a comparativeanalysis of competition policies in the two countries in the part of the workthat follows.